"An abnormal habit": Alcohol policy and the control of methylated spirit drinking in England in the 1920s and 1930s. (April 2015) - Moss, Stella
Abstract This paper is a case-study analysis of methylated spirit drinking in England in the 1920s and 1930s, focussing in particular on moral panic about deviant consumption and the development of policy-making. During the interwar years there emerged a statistically minor, but socially significant, culture of drinking methylated spirit – an industrial denatured alcohol – in socio-economically deprived urban communities. In the wake of (often hyperbolic) discourse about the considerable physical damage caused by methylated spirit consumption, and associated concerns about the perceived moral deviancy of drinkers, policy-makers developed a variety of regulatory strategies aimed at curbing consumption. Overall, this paper reveals the complex matrix of legislative, judicial and administrative regulation which framed responses to this widely vilified form of alcohol consumption, and in doing so points to some of the varied pressures and influences which informed harm-reduction policy-making.